Tornar-se catador: uma análise psicossocial - Miura, Paula Orchiucci Cerantola (2004)
The increase of the unemployment has increasingly contributed to the growth of the recyclable material collectors occupation in the streets of the big and medium Brazilian urban areas. In general, these people live on the edge of the social rights, excluded from the job market, with low rates of schooling and absence of all kind of technical capacitation, besides, many times, they have compromised health conditions. That being the case, the activity of collecting recyclable garbage represents one way of social insertion. Then the garbage and the collection constitute, in the middle of their lives, in their relationships and emotions, suffering and happiness. The present work has as objective to investigate how the social inclusion-exclusion process is particularized in these collectors everyday life, since the beginning of their exclusion history, in the school and familiar ambit, until the current occupation; analyzes intet personal relations links and breakups, distress, feelings, affections, and also the relation health-disease as one of the revealing dimensions of suffering. The information obtained was registered in field diary and record, being the research made through participant observation and semi-structured interviews. In the participant observation, the researcher followed the collectors in their everyday job activities and in their category meetings. The data analysis reveals that the collectors history of life is all marked by the social exclusion,and the current occupation reallyis, itself, another suffering among others already felt in previous times. The most frequent emotions are shame and humiliation,which specially come from the discrimination and prejudice. On the other hand, being a collector can also be a source of joy. On one side, for an ethical reason, that is to the possibility of the person to regain his own dignity to insert himself and to be socially recognized as honest worker, distinct from beggars and thieves. On the other side, for having been given the opportunity of organizing and mobilizing themselves together in the battle for better conditions of work and life, translated in the insistence of the group to make nationally official this job as a profession or, even, in changes of the proper routine of collecting recyclable material, which can be less isolated, more organized, cleaner and profitable. Moreover, they reveal feeling happiness when this activity allows them to obtain items until then inaccessible,as, for example, electrical appliances found in the garbage sometimes. About the health issue, these collectors do not believe that the collecting work is a risk indeed. For them, health, risk is, above all, not having food on the table, not having a place to live, neither having clothes to dress. They affirm that physical diseases caused by the work in the garbage can be treated; for the hunger, there is not cure. We can conclude that being a collector, mainly if he is member of an organized group, is a possibility of life potentialization for those who saw themselves excluded from the job market and without options, damaged in what refers to schooling and technical preparation